Human Resource Management in Teacher Recruitment: A Systematic Review - Dian Fadilla; Sopiah (Business and Investment Review, 2023)
The quality of education is driven by good human resources. Therefore, in preparing professional educators, every educational institution is required to have the ability and competence in accordance with their field and profession. This systematic literature review aims to analyze teacher recruitment management. Using the PRISMA principles, this literature review successfully identified 12 relevant studies derived from scopus indexed articles (Q1-Q4). The analysis grouped themes and displayed the interconnectedness of the emerging themes using Watase Uake software. The results of the systematic literature review show that research on teacher recruitment strategies is limited and that current teacher recruitment strategies are well-intentioned and likely to play a role in attracting new teachers, but little is known about their effectiveness, and little attention has been paid to important theories and research from sources outside education.